Critical Consciousness of Noon.Meem.Rashid - Rizwan Faisal (بازیافت, 2021)
<p class="MsoNormal" style="margin-bottom: .0001pt; text-align: justify; line-height: 150%; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt; background: white; mso-background-themecolor: background1;"><span style="mso-ascii-font-family: "Times New Roman"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: major-bidi; color: #222222; mso-fareast-language: EN-GB;">A study of Rashid's critical capital shows that Rashid's study was extensive. He has written on many aspects of literature. Rashid had a solid and reasoned view on various genres of literature. Although Rashid did not pay close attention to criticism, his articles reflect his deep critical consciousness. These articles reveal the tastes of the great poet of Urdu poetry. These articles by Rashid have been written in different periods. Therefore, Rashid's mental maturity looks different in different subjects. Rashid's style is solid, scientific and reasoned. They base their views on arguments and proofs beyond prejudice. Although Rashid did not pay attention to criticism, his articles are a thought-provoking addition to Urdu literature.